Pandemic vs. school – remote education in the Zespół Szkół Ogólnokształcących im. Juliusza Słowackiego (Schools of the Civic Educational Association) in Cracow - Zatorska, Dorota; Lech, Michał; Saja-Garbarz, Diana (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
Zespół Szkół Ogólnokształcących im. Juliusza Słowackiego (Schools of the Civic Educational Association) is an institution that unites a primary school, a secondary school of general education, and a kindergarten. Like the entire educational environment in Poland, in March 2020, the school complex faced decisions that required a change in the organization of norms, principles, habits, and mentality overnight to maintain the continuity of teaching. The first undertaken actions were the establishment of the school’s crisis management staff, numerous letters from the school principal addressed to the parents, teacher training, changing and adjusting the work hours, verifying students’ existing email addresses, and launching online learning platforms, as well as providing computer equipment to students in a difficult situation. The next step was to improve the quality of education and exchange of practices and experience between teachers. Regular meetings of teachers in educational teams and organizational groups began to take place. As a result of the prolonged period of isolation, difficulties have arisen requiring putting into effect the psychological and pedagogical support. At the times of improvement of the epidemiological situation in the country and partial lifting of the lock down, consultations were organized at the school for secondary school students and eighth-graders, the activities of the sports and tourism school association “Glosator” were used to organize sports activities in the sanitary regime. The working time of the youngest students at school, from integrated teaching, was used for the organization of a ski camp, and during the winter break, day camps were organized in accordance with the recommendations of the ministry.